Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpls.2021.715377
|View full text |Cite
|
Sign up to set email alerts
|

Homo- and Dikaryons of the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis Differ in Life History Strategy

Abstract: Arbuscular mycorrhizal fungi (AMF) are obligate plant symbionts that have the potential to improve crop yield. These multinucleate organisms are either “homokaryotic” or “dikaryotic”. In AMF dikaryons, thousands of nuclei originating from two parental strains coexist in the same cytoplasm. In other fungi, homokaryotic and dikaryotic strains show distinct life history traits (LHTs), such as variation in growth rates and fitness. However, how such traits compare between dikaryons and homokaryons of AMF is unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…irregularis (Chen et al ., 2018; Serghi et al ., 2021) that may have consequences for the symbiotic functions of the fungus. For example, it has been shown that the proportion and speed of spore germination are higher in homokaryons, while the hyphal network structure is more complex in dikaryons (Serghi et al ., 2021). In any case, the physiological mechanisms underlying the differences between AMF species is an aspect of Glomeromycotan biology that requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…irregularis (Chen et al ., 2018; Serghi et al ., 2021) that may have consequences for the symbiotic functions of the fungus. For example, it has been shown that the proportion and speed of spore germination are higher in homokaryons, while the hyphal network structure is more complex in dikaryons (Serghi et al ., 2021). In any case, the physiological mechanisms underlying the differences between AMF species is an aspect of Glomeromycotan biology that requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Other efforts aimed to disentangle the genetic basis of intra‐specific trait variability of R . irregularis (Chen et al ., 2018; Serghi et al ., 2021) that may have consequences for the symbiotic functions of the fungus. For example, it has been shown that the proportion and speed of spore germination are higher in homokaryons, while the hyphal network structure is more complex in dikaryons (Serghi et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both Rhizophagus and Funneliformis are considered generalists (Öpik et al, 2006;Smith & Read, 2008), Funneliformis may be better suited for the crops preceding potato on this land (wheat, kale, leeks, kale and pea), hence its presence in the field. Additionally, host status is not as simple as previously thought as the strain of fungal species can impact its generalist nature (Serghi et al, 2021). This can be driven by the diversity of cropping, with polycultures promoting the largest diversity of AMF (Guzman et al, 2021) and possibly establishing a richer community for future crops.…”
Section: Fungal Identity Drove the Impact Of Amf On Pcnmentioning
confidence: 99%
“…Early work measured fractal dimensions of mycelia at both micro- and macro-scales, and quantified their variation under different growth conditions or biotic interactions [ 15 , 16 ]. More recently, some researchers have systematically measured simple morphological traits (e.g., hyphal number and length, spore counting or branching frequency) and continuous growth parameters (e.g., hyphal extension rate and branching rates) using automated techniques to characterize trade-offs in hyphal morphology [ 17 ], life history [ 18 ], hyphal space-searching strategies [ 19 , 20 ] or to parametrize mathematical models of fungal colony growth [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%